2017
DOI: 10.4103/njcp.njcp_338_16
|View full text |Cite
|
Sign up to set email alerts
|

Hamartomatous polyp of the tonsil: A case report

Abstract: Hamartomatous polyps of the tonsil are rare. They have been described using various terms such as a lymphangiomatous polyp, lymphangiectatic fibrous polyp, lipomatous polyp, or pedunculated tonsil; hence, the actual incidence is difficult to be quantified. Polyp of the palatine tonsils is an unusual benign lesion of the head and neck. It is a rare polypoidal mass that generally arises from a pedicle attached to the tonsil and projecting into the oropharynx. Polypoid lesions of the head and neck are likewise ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Lymphangiomatous polyps are common in the low gastrointestinal tract, 3. However, tonsillar lymphangiomatous polyps are rare entities with sparse reports in the literature, 1–19. Nevertheless, most authors agree that this condition has a higher incidence than reported because these masses can be overlooked in a routine examination and because of inconsistencies with their classification 1–6.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lymphangiomatous polyps are common in the low gastrointestinal tract, 3. However, tonsillar lymphangiomatous polyps are rare entities with sparse reports in the literature, 1–19. Nevertheless, most authors agree that this condition has a higher incidence than reported because these masses can be overlooked in a routine examination and because of inconsistencies with their classification 1–6.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, they are polypoid, but sessile lesions have also been described 1 10. The age of appearance varies, but it seems more common during the second decade of life,1–19 contrary to the typical lymphangiomas that are usually present at or around the time of birth 2. Most series do not show any sex or laterality predilection;1 10 however, a recent study supports a 1.4:1 male to female ratio 21.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations